Anticancer mechanism of Pisangulin angulata through in silico and development as teaching material - Agus Muji Santoso; Bayu Guruh Binangkit; Mohamad Amin; Sutiman Bambang Sumitro; Betty Lukiati; Mumun Nurmilawati; Poppy Rahmatika Primandiri; Ida Rahmawati; S Sulistiono; Yayoi Kodama (Universitas Negeri Jakarta, 2019)
This study aims to reveal the anticancer mechanism of the bioactive compound of Pisangulin angulata and to assess the feasibility of that results as teaching material. This research includes descriptive explorations. In the first stage, an in silico analysis was performed by molecular docking method between physalin compounds and GLI1 protein. The second steps of this study aim to develop teaching materials based research using the Analysis, Reorganizing, Piloting Class, and Evaluating (ARPE models). Feasibility test was carried out by experts and practitioners. Think Pair Share was used in the pilot project. Student motivation and misconception were recorded using SMI and CRI instrument. This study reveals that physalin B has higher activities than controls. The type of chemical bond that is formed between GLI1 amino acids residues with physalin is hydrogen bonds and hydrophobic bonds. The visualization of the types of bonds in that molecular docking between GLI1 amino acid residues and physalin has a high degree of feasibility (89) and can be used to enrich Chemistry for Biology lectures. The visualization of these chemical bonds can increase learning motivation and can improve the understanding of the concept of chemical bonds.